2014
DOI: 10.1071/py12118
|View full text |Cite
|
Sign up to set email alerts
|

Australian practice nurses’ perceptions of their role and competency to provide nutrition care to patients living with chronic disease

Abstract: Nutrition is important in the management of chronic disease, and practice nurses in the Australian primary care setting are increasingly providing nutrition care to patients living with chronic disease. The aim of the present study was to investigate practice nurses' perceptions of their role and competency to provide nutrition care to patients living with chronic disease in Australia. Twenty practice nurses currently employed in general practice participated in an individual semi-structured telephone intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 21 publications
2
52
0
1
Order By: Relevance
“…Of a total of five qualitative papers, three conducted interviews with nurses (Persson & Martensson , Aranda & McGreevy , Cass et al . ); one conducted interviews and observations at facilities (Faugier et al . ) and one used interviews and focus groups (Phiri et al .…”
Section: Resultsmentioning
confidence: 99%
“…Of a total of five qualitative papers, three conducted interviews with nurses (Persson & Martensson , Aranda & McGreevy , Cass et al . ); one conducted interviews and observations at facilities (Faugier et al . ) and one used interviews and focus groups (Phiri et al .…”
Section: Resultsmentioning
confidence: 99%
“…Negative patient attitudes towards diet were considered disincentives to offering dietary advice (Cass et al . ).…”
Section: Impact Of Initiatives To Promote High‐fibre/wholegrain Foodsmentioning
confidence: 97%
“…The review found that nurses recognise the importance of nutritional care in preventing and managing disease (21,22) and acknowledge that nutritional care is an important part of their role (23)(24)(25) . However, studies have consistently found obstacles to the delivery of nutritional care by nurses, which include: (i) lack of knowledge, (ii) lack of clarity regarding the nursing role in nutritional care and (iii) lack of confidence in the effectiveness of nutritional care interventions.…”
Section: Review: Evidence Of the Effect Of Nurse Nutritional Carementioning
confidence: 99%
“…It has also been found amongst the hospital nurses in Turkey (22) and Australia (28) . Australian practice nurses believe that they have a low level of nutrition knowledge (21) . In contrast, care home staff in Wales drew on their personal knowledge of nutrition striving to provide personalised care in partnership with families and were found to assume that they had knowledge of what constitutes a healthy diet for older people.…”
Section: Lack Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation